2011
DOI: 10.1177/1362361311413397
|View full text |Cite
|
Sign up to set email alerts
|

The association of autism diagnosis with socioeconomic status

Abstract: In the US state of New Jersey, ASD prevalence is higher in wealthier census tracts, perhaps due to differential access to pediatric and developmental services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
113
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(136 citation statements)
references
References 26 publications
(35 reference statements)
16
113
2
5
Order By: Relevance
“…This finding is in keeping with that of Maureen et al who noted a high prevalence of autism among parents from a high socio-economic class.care-giving 33 Autism has been positively associated with high socioeconomic status (SES) in at least eight epidemiological studies from different populations and in different ethnic backgrounds. 12,13,34,35 , while two Scandinavian studies did not find that association. care-giving 34 Although the causal basis for these associations with autism are unclear, many autism studies have suggested that they may be related to access to health resources, in the context of higher income and/ or education, influencing increasing autism diagnosis.…”
Section: Resultsmentioning
confidence: 83%
“…This finding is in keeping with that of Maureen et al who noted a high prevalence of autism among parents from a high socio-economic class.care-giving 33 Autism has been positively associated with high socioeconomic status (SES) in at least eight epidemiological studies from different populations and in different ethnic backgrounds. 12,13,34,35 , while two Scandinavian studies did not find that association. care-giving 34 Although the causal basis for these associations with autism are unclear, many autism studies have suggested that they may be related to access to health resources, in the context of higher income and/ or education, influencing increasing autism diagnosis.…”
Section: Resultsmentioning
confidence: 83%
“…The higher socioeconomic representation of parents, where 75.7% of fathers were in professional or skilled occupations is probably the result of selective access to the intervention programme. At the same time, an interesting fact is that a national community based epidemiological study in United States reported a higher prevalence of autism in wealthier counties, but this too was explained on differential access to services 20 . Other reports have failed to find a relationship between autism and socioeconomic factors 21 .…”
Section: Discussionmentioning
confidence: 98%
“…Mainly in American studies, a higher SES, using proxies such as maternal income, occupation and education, was associated with ASD. 172,[240][241][242] However, when researchers in one of these studies conducted a subanalysis by case ascertainment, no association with SES was found using case ascertainment only from school sources. 242 In an Australian study, 172 maternal residence in remote areas was negatively correlated with cases of ASD without intellectual disability (ID).…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…The importance of SES emerged as a predictor of ASD risk in nine studies, 102,119,172,[240][241][242][243][244][245] but findings were mixed. Mainly in American studies, a higher SES, using proxies such as maternal income, occupation and education, was associated with ASD.…”
Section: Socioeconomic Statusmentioning
confidence: 99%